Dietary fiber and fatty acids may impact clinical outcomes in pediatric obesity-associated asthma: insights from the SOAP study - Al-Dasooqi, Dena Samir; Shailesh, Harshita; Djekidel, Mohamed Nadhir; Alabduljabbar, Shaikha; Ahmed, Salma Hayder; Olabi, Yasmin; Shallouf, Nour; Hani, Yahya; Janahi, Ibrahim; Terranegra, Annalisa (Frontiers in Nutrition, 2025)
Background and aimsEvidence suggests that diet influences the pathophysiology of asthma, but its role in pediatric obesity-related asthma is unclear. This case–control study aimed to explore the relationships between nutrient intake and the pathophysiology of asthma in children who are overweight or obese.MethodsParticipants of the Sphingolipids in Childhood Asthma and Obesity study (100 children aged 6–17 years) were divided into four groups: normal weight with asthma (NW-A, n = 16); overweight or obese with asthma (OO-A, n = 26); normal weight (NW, n = 33); overweight or obese (OO, n = 25). Dietary intake was recorded via 3-day food diaries. Diet quantity and quality were assessed using UK Government Dietary Recommendations and dietary inflammatory index (DII) scores. Nutrient intake was compared across groups, and regression analyses were applied to identify the top contributors to asthma and obesity-associated asthma. Correlation analyses were used to assess the associations between the most important nutrients and clinical parameters.ResultsFatty acids (FAs), including saturated, monounsaturated, and polyunsaturated FAs, were identified as the most significant contributors to asthma and obesity-associated asthma, followed by several vitamins, fibers, and sugars. The relationships between nutrients and clinical parameters showed different patterns in the NW-A and OO-A groups. In NW-A, intakes of saturated, monounsaturated, and polyunsaturated FAs, including α-linolenic acid (PUFA 18:3, n-3), were positively associated with vital capacity and total lung capacity and inversely related to plasma levels of interleukin (IL)-10; while soluble fiber intake was negatively correlated with lung clearance index. In OO-A, FAs, including linoleic acid (PUFA 18:2, n-6) and α-linolenic acid, and vitamin E isoforms were positively associated with vital capacity, total lung capacity, inspiratory capacity, and forced vital capacity, and negatively associated with lung clearance index and forced expiratory volume in 1 s. Multiple saturated FA intakes were negatively associated with levels of IL-10, IL-17A, and IL-2.ConclusionThis study suggests that certain dietary components, such as FAs and fiber, may have different effects on asthma in overweight or obese children compared to normal weight children. Thus, tailored dietary modifications, guided by body mass index, could improve asthma symptoms. Randomized controlled trials are needed to confirm these associations and guide dietary recommendations.